Analisis Keberhasilan Kabupaten Kepulauan Meranti Pasca Pemekaran Daerah di Bidang Ekonomi dan Pelayanan Publik - Oges Susfita Putri; Nathasia Angelina Saragi; Sella Oktapatika; Calvin Antony; Aditya Saputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The success of Meranti Islands Regency after the expansion of Bengkalis Regency which occurred on December 19 2008, with a focus on the economic sector and public services. Even though there are several indicators of better economic performance compared to the parent region, the overall economic growth of Meranti Islands Regency is still lagging behind. On the public service side, even though it shows more positive results, there are several indicators that are still lower than Bengkalis Regency. This research uses literature studies to identify the challenges and performance of the Meranti Islands Regency, including the problem of fiscal dependence and suboptimal regional financial management. Public services in this area have not been effective due to inefficient use of funds, lack of public service energy, and service utilization that has not been maximized. Despite the accessibility of public services.